PERAN GURU DALAM MENINGKATKAN KUALITAS BACA AL-QUR’AN DI TPQ AR-RIDLO JOMBANG - Rahman Hakim, Arif; Nurul Qomaria, Elysa; Khodiriyah, Putri (ILJ: Islamic Learning Journal, 2023)
The teacher is a professional educator, who educates, teaches a science, guides, trains, gives assessments, and evaluates students. The Al-Qur'an Education Park teacher at TPQ Ar Ridlo Jatirejo Jombang plays a very strategic and significant role in teaching the Al-Qur'an to students. This type of qualitative research with interview, observation and documentation methods. The role of the teacher in improving the quality of Al-Qur'an reading at TPQ Ar Ridlo, as an educator, the teacher creates good conditions during the Al-Qur'an learning process, by applying various learning methods of baghdadiyah, sorogan and habituation methods. As an example, the teacher should be a figure who can be a role model for all students, especially in relation to learning the Qur'an. As a motivator, the teacher at TPQ Ar Ridlo seeks to foster motivation, to encourage students to learn to read the Koran. As an evaluator, the teacher collects data or information about the successful learning of the Qur'an that has been carried out. Factor supporters and obstacles in improving the quality of reading the Koran at TPQ Ar-Ridlo, the process of learning the Koran will not work just like that without a teacher who is a fighter and has good competence. Facilities are available in the form of tables, blackboards and teaching aids as well as pointing devices, iqro books, Al-Qur'an, recitation books, tilawati handbooks, student achievement cards to support Al-Qur'an learning. Parents who pay little attention to their children, are indifferent, do not pay attention to their children's learning progress will certainly hinder their children's success in learning the Qur'an. In a less harmonious TPQ environment, children who are bullied will have pressure that hinders the progress of children learning the Qur'an.